Barovariability - Sanjay Kalra; Nishant Raizada; Saptarshi Bhattacharya; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
Barovariability is defined as the variation or changes that occur in weight, over a specific time frame, in persons living with obesity or overweight. This includes physiological alteration in weight, as well as pathological weight cycling or yo yo phenomenon. Barovariability can be diagnosed by regular weight and body composition monitoring, and may be predicted by artificial intelligence (AI) tools. Exercise barovariability is associated with adverse psychosocial as well as biomedical outcomes. A realistic and rational approach towards weight management can help prevent and mitigate barovariability. Keywords: GLP1RA, obesity, overweight, psychosocial weight management, behavioural therapy.